Molecular mechanisms of exercise intervention in alleviating the symptoms of autism spectrum disorder: Targeting the structural alterations of synapse - Zong, Wenhao; Lu, Xiaowen; Dong, Guijun; Zhang, Li; Li, Kefeng (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is a complex and heterogeneous neurodevelopmental disorder characterized by stereotyped behaviors, specific interests, and impaired social and communication skills. Synapses are fundamental structures for transmitting information between neurons. It has been reported that synaptic deficits, such as the increased or decreased density of synapses, may contribute to the onset of ASD, which affect the synaptic function and neuronal circuits. Therefore, targeting the recovery of the synaptic normal structure and function may be a promising therapeutic strategy to alleviate ASD symptoms. Exercise intervention has been shown to regulate the structural plasticity of synapses and improve ASD symptoms, but the underlying molecular mechanisms require further exploration. In this review, we highlight the characteristics of synaptic structural alterations in the context of ASD and the beneficial effects of an exercise intervention on improving ASD symptoms. Lastly, we explore the possible molecular mechanisms of improving ASD symptoms through exercise intervention from the perspective of regulating synaptic structural plasticity, which contributes to further optimizing the related strategies of exercise intervention promoting ASD rehabilitation in the future.